"They'll Always Find a Way to Get to You": Technology Use in Adolescent Romantic Relationships and Its Role in Dating Violence and Abuse. Issue 14 (July 2017) - Stonard, Karlie E.; Bowen, Erica; Walker, Kate; Price, Shelley A.
Electronic communication technology (ECT), such as mobile phones and online communication tools, is widely used by adolescents; however, the availability of such tools may have both positive and negative impacts within the context of romantic relationships. While an established literature has documented the nature, prevalence, and impact of traditional forms of adolescent dating violence and abuse (ADVA), limited empirical investigation has focused on the role of ECT in ADVA or what shall be termed technology-assisted adolescent dating violence and abuse (TAADVA) and how adolescents perceive the impact of TAADVA relative to ADVA. In this article, the authors explore the role ECT plays in adolescent romantic relationships and psychologically abusive and controlling ADVA behaviors and its perceived impact. An opportunity sample of 52 adolescents (22 males and 30 females) between the ages of 12 and 18 years participated in the study. One all-female and seven mixed-gendered semi-structured focus groups were conducted. Thematic analysis was used to identify three superordinate themes, including (a) perceived healthy versus unhealthy communication, (b) perceived monitoring and controlling communication, and (c) perceived impact of technology-assisted abuse compared with that in person. While ECTs had a positive impact on the development and maintenance of adolescent romantic relationships, such tools also provided a new avenue for unhealthy, harassment, monitoring, and controlling behaviors within these relationships. ECT was also perceived to provide unique impacts in terms of making TAADVA seem both less harmful and more harmful than ADVA experienced in person. Adolescents' perceptions and experiences of ECT in romantic relationships and TAADVA may also vary be gender. Implications of the findings are discussed, and recommendations are made for future research.